1997
DOI: 10.1002/pro.5560061201
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge‐based model of a glucosyltransferase from the oral bacterial group of mutans streptococci

Abstract: Mutans streptococci glucosyltransferases catalyze glucosyl transfer from sucrose to a glucan chain. We previously identified an aspartyl residue that participates in stabilizing the glucosyl transition state. The sequence surrounding the aspartate was found to have substantial sequence similarity with members of a-amylase family. Because little is known of the protein structure beyond the amino acid sequence, we used a knowledge-based interactive algorithm, MACAW, which provided significant level of homology w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
21
0

Year Published

2005
2005
2011
2011

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 64 publications
(23 citation statements)
references
References 39 publications
2
21
0
Order By: Relevance
“…More than 50% of the infected animals showed a significant increase in responses reactive with the HDS peptide. This 19-mer peptide is associated with the beta 7 strand element of the putative (beta, alpha) 8 catalytic barrel domain of Gtf (8) and contains a catalytically essential histidine residue (His 461 in S. mutans GtfB) (42). Site-directed mutagenesis of a nearby aspartate (Asp 467 in S. mutans GtfB) within the HDS-associated Gtf sequence altered the water solubility of the glucan synthesized from sucrose (29).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…More than 50% of the infected animals showed a significant increase in responses reactive with the HDS peptide. This 19-mer peptide is associated with the beta 7 strand element of the putative (beta, alpha) 8 catalytic barrel domain of Gtf (8) and contains a catalytically essential histidine residue (His 461 in S. mutans GtfB) (42). Site-directed mutagenesis of a nearby aspartate (Asp 467 in S. mutans GtfB) within the HDS-associated Gtf sequence altered the water solubility of the glucan synthesized from sucrose (29).…”
Section: Discussionmentioning
confidence: 99%
“…Three monoepitopic peptide construct sequences (Pep 7, Pep 11, and Pep 16) were based on predicted MHC class II epitopes that were in the Gtf sequence, using the ProPred algorithm. Five monoepitopic peptide construct sequences (GGY, CAT, HDS, LVK, and VMAD) were based on Gtf sequences associated with putative catalytic interactions (8,9,(22)(23)(24)42). Two monoepitopic peptide construct sequences (GLB and GLU) were based on Gtf sequences associated with putative glucan binding domains in the C-terminal third of the Gtf protein (1,17,43).…”
Section: Animals For the Immunization Experimentmentioning
confidence: 99%
See 1 more Smart Citation
“…Secondary structure predictions suggest that the Gtfs are members of the ␣-amylase superfamily and contain a circularly permuted (␣/␤) 8 -barrel motif (8,19,26). Our results in Fig.…”
Section: Discussionmentioning
confidence: 59%
“…Since these observations suggested that the primary CAT site existx inside the (␣/␤) 8 -barrel structure, it was thought that this region may be difficult to recognize as an antigen for the immune system, although low-molecular-weight sucrose is able to pass through this structure as an enzyme substrate. Thus, it was suggested that the antigenicity of CAT would be low, as shown by Parker's prediction.…”
mentioning
confidence: 99%